Economic Valuation of Agricultural Productivity Enhancement through Digital-Based Resource Conservation - Annisa Ilmi Faried; Vina Arnita; Nisa Ulzannah (CV. Raskha Media Group, 2025)
The agricultural sector faces increasing pressure to enhance productivity while maintaining the sustainability of natural resources. Digital technologies offer significant opportunities to optimize resource use and support conservation-oriented farming systems, yet their economic value is often insufficiently quantified. This study examines the economic valuation of agricultural productivity enhancement through digital-based resource conservation. Using a conceptual–analytical approach supported by evidence from recent empirical studies, this paper integrates economic valuation frameworks with digital agriculture practices, including precision farming, data-driven resource management, and decision-support technologies. The analysis highlights how digital interventions generate direct financial benefits through productivity gains and cost efficiency, as well as indirect values related to ecosystem services, option values for future innovation, and social welfare improvements. The findings indicate that digital-based resource conservation contributes not only to higher agricultural output but also to long-term sustainability by reducing environmental degradation and enhancing adaptive capacity to climate change. This study provides a comprehensive valuation perspective that supports policy formulation and strategic investment in digital agriculture systems. The results underscore the importance of incorporating economic valuation into agricultural system planning to ensure balanced outcomes between productivity growth and resource conservation